Management of trimalleolar fracture in Sanglah hospital: a case series - Subawa, I Wayan; Ambong, Hafidz Addatuang; Wibowo, Trimanto; Putra, I Gede Mahardika (International Journal of Research in Medical Sciences, 2018)
Trimalleolar fractures are one of the most complex fracture around ankle. This study aims to assess the functional outcome and result of the surgical treatment for trimalleolar fracture. Case 1: A 49-years-old male experience closed fracture left ankle Lauge-Hansen PER type IV caused by traffic accident. Patient present with swollen and painful around ankle with an inability to bear weight on the affected extremity. Case 2: A 36-years-old female sustained closed fracture at right trimalleolar ankle, closed fracture at right talus nondisplace Hawkins I, and closed fracture at second, third, and fourth metatarsal. Case 3: A 57-years-old female came with history the left ankle twisted after got slipped and fell down at the yard. Patient was diagnosed by closed fracture left ankle Lauge Hansen SER type IV. Ankle fracture mostly happen in young men and older women during sporting activities or even bicycle or car accidents. The Lauge-Hansen system classify the fracture based on the postion and the direction of the ankle when trauma happen. The AOFAS was use for evaluation patient-relevant outcomes in patients operated on with anatomical ankle injury. In or present study of 3 patients with ankle fractures that were unstable, displaced or both treated surgically by open reduction with internal fixation in accordance with Lauge-Hansen classification. The result in our series confirm that all of 3 patients have a good result based on AOFAS scoring for evaluation the treatment and it means the management approve the good functional outcomes for the patients with ankle fractures.